Anisotropic Cell Expansion Is Affected through the Bidirectional Mobility of Cellulose Synthase Complexes and Phosphorylation at Two Critical Residues on CESA3 . Issue 1 (11th March 2016) - Chen, Shaolin; Jia, Honglei; Zhao, Heyu; Liu, Dan; Liu, Yanmei; Liu, Boyang; Bauer, Stefan; Somerville, Chris R.
Abstract : Phosphorylation of a subunit of cellulose synthase differentially alters the rate at which cellulose synthase moves in both directions along microtubules, thereby impacting growth and development. Abstract: Here we report that phosphorylation status of S211 and T212 of the CESA3 component of Arabidopsis ( Arabidopsis thaliana ) cellulose synthase impacts the regulation of anisotropic cell expansion as well as cellulose synthesis and deposition and microtubule-dependent bidirectional mobility of CESA complexes. Mutation of S211 to Ala caused a significant decrease in the length of etiolated hypocotyls and primary roots, while root hairs were not significantly affected. By contrast, the S211E mutation stunted the growth of root hairs, but primary roots were not significantly affected. Similarly, T212E caused a decrease in the length of root hairs but not root length. However, T212E stunted the growth of etiolated hypocotyls. Live-cell imaging of fluorescently labeled CESA showed that the rate of movement of CESA particles was directionally asymmetric in etiolated hypocotyls of S211A and T212E mutants, while similar bidirectional velocities were observed with the wild-type control and S211E and T212A mutant lines. Analysis of cell wall composition and the innermost layer of cell wall suggests a role for phosphorylation of CESA3 S211 and T212 in cellulose aggregation into fibrillar bundles. These results suggest that microtubule-guided bidirectional mobility of CESA complexes is fine-tuned by phosphorylation of CESA3 S211 and T212, which may, in turn, modulate cellulose synthesis and organization, resulting in or contributing to the observed defects of anisotropic cell expansion.